Highly branched poly(β-amino ester) delivery of minicircle DNA for transfection of neurodegenerative disease related cells - Shuai Liu (Nature Portfolio, 2019)
Therapeutics delivery by using non-viral vectors presents several challenges in the design of an appropriate polymeric structure. Here, the authors report a series of highly branched, biodegradable polymers which show high transfection efficiency in human multipotent adipose derived stem cells and primary astrocytes.